Childhood Uveitis - Thurau, Stephan (Klinische Monatsblätter für Augenheilkunde, 2020)
Childhood uveitis is an ophthalmological challenge, since on the one hand it often remains asymptomatic and difficult to detect, and on the other hand it often has a chronic course and is associated with a high risk of complications threatening the vision. The most important risk factors for childhood uveitis are underlying rheumatic diseases; recommendations for ophthalmological monitoring have been developed together with paediatric rheumatologists. Intermediate and posterior uveitis are rare in children. The therapy must effectively control inflammation and at the same time cause only minimal side effects. Since steroids in particular cause side effects frequently, an immunosuppressive therapy must be initiated early in an interdisciplinary cooperation with paediatric rheumatologists and parents with the goal of minimising steroids.Die Uveitis im Kindesalter ist eine ophthalmologische Herausforderung, da sie einerseits häufig symptomlos bleibt und schwer zu erkennen ist und andererseits vielfach chronisch verläuft sowie mit einem hohen Risiko für visusbedrohende Komplikationen behaftet ist. Die wichtigsten Risikofaktoren für eine Uveitis im Kindesalter sind rheumatische Grunderkrankungen; gemeinsam mit den Kinderrheumatologen wurden Empfehlungen für die ophthalmologische Überwachung erarbeitet. Intermediäre und posteriore Uveitiden sind bei Kindern selten. Die Therapie muss Entzündung effektiv kontrollieren können, darf aber gleichzeitig nur ein Minimum an Nebenwirkungen verursachen. Da gerade die Steroide häufig Nebenwirkungen verursachen, muss frühzeitig in interdisziplinäre Zusammenarbeit mit Kinderrheumatologen und Eltern eine immunsuppressive Therapie mit dem Ziel der Steroidminimierung eingeleitet werden.
Keywords: uveitis; paediatric ophthalmology; therapy